Conditionalities of Public Microfinance and the Rural Poor: Voices From the Below. (10th March 2020) - Chowdhury, Mohammad Shahjahan; Ahmmed, Faisal; Hossain, Md. Ismail
Abstract: This paper examines microfinance conditionalities of the Bangladesh Rural Development Board in Bangladesh from clients' and providers' perspectives based on a qualitative case study. The study reveals that the credit is less poor focus in terms of amount and disbursement procedure. Additionally, group liability and cooperatives are used as tactics for surveillance and punishment instead of invigorating collective effort. Saving and share work as disciplinary instruments instead of capital accumulation. Besides, service is regarded as a conditional commodity, and skill development becomes individual responsibility. The study implies listening to the voice of the poor and redesigning antipoverty programmes based on the need felt by them. © 2020 John Wiley & Sons, Ltd.